The Possibility and Cause of Relapse After Previously Recovering From COVID-19: A Systematic Review - Elsayed, Sarah M (Cureus, 2020)
The severe acute respiratory distress syndrome coronavirus-2 (SARS-Cov-2) is a novel coronavirus that is believed to be mainly transmitted via droplet and contact transmission. While research is focusing on epidemiology, transmission, vaccine development, and therapeutics for coronavirus disease 2019 (COVID-19), there is a possibility of disease relapse. There are reports of patients who tested positive for SARS-Cov-2 after clinical recovery and initial clearance of the virus. Objective This systematic review aims to identify the trends of COVID-19 relapse, the effects of co-morbidities on it, and associated mortality rates. Methods We conducted a systematic search during March and April 2020 for research articles on the relapse of COVID-19 using two primary databases, PubMed and Embase. Results A total of 13 eligible studies were screened of which 11 (case reports) were eligible for data extraction. The earliest to report relapse was after two days of discharge and the latest was 22 days after discharge. The mean number of days to relapse was 12 days and the median number was seven days. There was incomplete information about comorbidities. No mortalities were reported at the time of the study.